(3TQM GdTGajIs - (3CMeO Hf GdMSf Hf jhSa, aNQ GdOjf GdLGQHQOj , (B746 (3g` s; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdEeGe GdLGQHQOi deG cGf cJGH GdJUQja GdPi Ufag GdaGVd GHf GdMGLH s
(3BNQgG (B:s
(3deYfGgG ai GdZGjI hGdEfJgGA hGddg CYde HGdUhGH Je GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdUQas